Atrioventricular Septal Defects Repair: Comparison of Classic Single Patch and Double-Patch Techniques - Kanat Özışık; Gökçe Selçuk Sert; Yasemin Özdemir Şahan; Ahmet Vedat Kavurt; Mustafa Yılmaz; Ata Niyazi Ecevit; Başak Soran Türkcan; Atakan Atalay (Genel Tıp Dergisi, 2023)
Objective: Different patch techniques were virtually always used in the surgery of pediatric patients with complete atrioventricular septal defects. In this study, we described our single center, single surgeon experiences and results about the classic single patch and double patch techniques to repair complete atrioventricular septal defects. Materials and Methods: This retrospective descriptive study included 30 patients who underwent intracardiac repair of complete atrioventricular septal defect in Ankara Bilkent City Hospital Department of Pediatric Cardiovascular Surgery. The study was conducted between February 2019 to December 2021. Patients in group S underwent surgery using the traditional single-patch method, while group D included patients who underwent repair using the double patch approach (n = 10). Patients’ demographic and clinical information was taken from institutional databases and medical records. Postoperative complications were recorded. Results: When the preoperative/postoperative insufficiency levels of the valves were compared with the Wilcoxon Signed rank test, the findings were not statistically significant for the left atrioventricular valves, but were statistically significant for the right atrioventricular valves. (p=0.02) When we compared postoperative valve regurgitation of both techniques with the Kruskall-Wallis test, no significant difference was found between postoperative valve regurgitation and function, independent of preoperative findings. Conclusion: Both operation techniques did not make a difference between operative or late mortality and morbidity. Depending on the surgeon’s experience, ventricular septal defect size does not play a restrictive role in the selection of the technique to be used. The single-patch and double patch method as described here is methodical, comprehensible, repeatable, and reasonably long-lasting.